Bimetallic-MOF derived nickel-iron phosphide nanosheets on carbon cloth for efficacious oxygen evolution reaction. (15th October 2022) - Chai, Ruiqing; Zhou, Tianqing; Sun, Daolai; Luo, Yuhong; Li, Jingde; Wu, Feichao
Abstract: It is of momentously realistic significance to exploit highly efficacious and cost-effective non-noble metal electrocatalysts for oxygen evolution reaction (OER), considering its promising renewable energy application. Herein, a self-supporting electrocatalyst composed of nickel-iron phosphide nanosheets on carbon cloth (NiFeP@CC) is proposed for OER, which are derived from the phosphating treatment of two-dimensional NiFe-MOF nanosheets. The NiFeP@CC composite possesses the synergistic effect of bimetallic NiFe phosphides in promoting the OER, the fully exposed active sites of the nano-sheet structure and the fast charge/mass transfer from the hierarchical porous structure. Owing to the above structural features, the optimized NiFeP@CC presents an impressive OER performance in alkaline solution. The overpotential and Tafel slope are as low as 229 mV and 36.4 mV dec −1 under a current density of 10 mA cm −2, respectively, much superior to those for the commercial IrO2 catalyst. More excitingly, this self-supporting electrocatalyst also possesses an exceptionally high durability, showing no activity degradation for 25 h. This work offers a simple and feasible strategy for developing practically available OER catalysts with a high activity and stability. Graphical abstract: Image 1 Highlights: A self-supporting electrocatalyst of NiFeP nanosheets on carbon cloth was developed. The NiFe phosphides and the hierarchically nano-sheet structure jointly promote OER. The electrocatalyst delivers an impressive OER performance in alkaline solution.